The assistance of Er,Cr:YSGG laser in pulp injury related to anterior teeth trauma - Balan, Gülşah; Peteers, Harry Huiz; Akyüz, Serap (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Erbium chromium or erbium lasers constitute preferred instruments for the preparation of that section of tooth adjacent to the pulp chamber rather than high-speed drills, especially in cases of dental injury. Their advantages can support modified operations in achieving optimum recovery and avoiding complications related to the healing process. Purpose: The aim of the study was to describe another modality of the assistance of erbium, chromium:yattrium-scandium-gallium-garnet (Er,Cr:YSGG) laser in traumarelated pulp injury affecting the anterior teeth. Case(s): The results of laser treatment applied to four pulp injuries of three children were analyzed in this case report. Case Management: Er,Cr:YSGG laser-assisted cavity preparation was performed without resort to a local anesthetic, the cavities being sealed with mineral trioxide aggregate (MTA). None of the cases demonstrated symptomatic or peri-radicular pathology during clinical or radiographic examinations. Conclusion: The results contained in this case report support the application in pediatric dentistry of a Er,Cr:YSGG laser to pulpotomy cavities as part of the treatment of traumatic pulpal injuries to permanent incisors.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />